Molecular dynamics simulations of the tensile responses and fracture mechanisms of Ti2AlN/TiAl composite. (June 2019) - Han, Xiuli; Liu, Pei; Sun, Dongli; Wang, Qing
Graphical abstract: Highlights: Interface atomic structure has a significant influence on the tensile fracture behavior of Ti2 AlN/TiAl composite. The Ti2 AlN/TiAl composite with coherent interface shows a brittle fracture behavior. The Ti2 AlN/TiAl composite with incoherent interface shows a ductile fracture behavior. Abstract: In the present work, molecular dynamics simulations are carried out to investigate the tensile responses and fracture mechanisms of Ti2 AlN/TiAl composite. It is found that the Ti2 AlN/TiAl composite with different interface atomic structure shows significantly different tensile responses and fracture mechanisms. When the tensile loading is applied normal to the Ti2 AlN(0 0 0 1)/TiAl(1 1 1) coherent interface, the micro-void would nucleate from the interface, rapidly propagate along the interface and evolve into the complete-crack, leading to the brittle fracture behavior of Ti2 AlN/TiAl composite. The formation of stress concentration and Lomer-Cottrell lock in the misfit dislocations at the coherent interface is the major mechanism for the nucleation of micro-void. When the tensile loading is applied normal to the Ti2 AlN(1 0  1 ¯  3)/TiAl(1 1 1) incoherent interface, micro-voids can nucleate from the weak interactive regions at the incoherent interface, but they cannot propagate rapidly along the incoherent interface, which indicates that the Ti2 AlN(1 0  1 ¯  3)/TiAl(1 1 1) incoherent interface system shows ductile fracture behavior. The ductile fracture mechanism is twofold: firstly, the dislocations in Ti2 AlN and TiAl slab can nucleate at the tip of micro-crack and effectively blunt the propagation of micro-crack along the incoherent interface; secondly, the strong NTi and NAl bonds at the incoherent interface can give a contribution to the overall stability of Ti2 AlN(1 0  1 ¯  3)/TiAl(1 1 1) incoherent interface.